Peningkatan Pengetahuan dan Praktikum Dasar-Dasar Microsoft Office di Panti Asuhan Abdi Agape Pontianak - Daniel Oktodeli Sihombing; Fitri Yutika; Fry Melda Saragih (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), Univesitas Kristen Indonesia, 2023)
Community Service (PKM) carried out by the PKM Team of the Sabda Setia Institute of Technology and Business (ITBSS) is a Microsoft Office Basic Training activity at the Abdi Agape Orphanage Pontianak. This activity has been carried out for three sessions over two days, namely on October 8 and 9, 2022. This Community Service activity was attended by 19 participants who are foster children at the Abdi Agape Orphanage Pontianak. This Microsoft Office Basic Training consists of three training topics on Microsoft Word, Microsoft Excel and Microsoft PowerPoint. These materials will be mentored by lecturers from the Sabda Setia Institute of Technology and Business. Based on the results of the evaluation and analysis of the Pre-test and Post-test scores, this Community Service activity succeeded in providing understanding for the training participants, as well as improving the abilities of the foster children at the Abdi Agape Orphanage, Pontianak. In this Microsoft Word Basic and Practical Training, the average Post-test score of the participants in the training increased by 30.05% from their Pre-test average. Then for Microsoft Excel Basic and Practical Training, the average Post-test score of participants in the training increased 21.82% from their Pre-test average score. Meanwhile, for the last session, namely Microsoft PowerPoint basic training, the average Post-Test score of participants in the training increased by 30.24%. Based on the test results that show this improvement, it can be said that the objectives and benefits of the Community Service Activities carried out at the Abdi Agape Orphanage Pontianak have been achieved. Keywords: Community Service; Microsoft Office; Word; Excel and PowerPoint.